АНАЛІЗ СТАНУ НЕДЕРЖАВНОГО ПЕНСІЙНОГО ЗАБЕЗПЕЧЕННЯ В УКРАЇНІ: ПРОБЛЕМИ, ПОТЕНЦІАЛ ТА МАКРОЕКОНОМІЧНИЙ ВПЛИВ - BASHUTSKYY, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to a comprehensive analysis of the state and prospects of the private pension provision system in Ukraine, the relevance of which increases under conditions of demographic ageing, financial instability, and martial law. The purpose of the study is to assess the role of private pension funds in generating long-term investment resources and to determine their potential impact on macroeconomic stability. The methodological basis of the research includes time series analysis, international comparisons, statistical generalizations, and scenario modelling of private pension fund assets up to 2030. The information base consists of data from the National Securities and Stock Market Commission of Ukraine, the State Statistics Service of Ukraine, the OECD, and the World Bank. The study reflects the dynamics of assets, contributions, and payments of private pension funds for 2019-2024, the structure of their investment portfolios, and population coverage. The key problems of the system are identified, among which are low public trust, insufficient tax incentives, underdeveloped capital markets, and the significant influence of martial law on investment activity. International comparisons demonstrate Ukraine’s considerable lag behind EU countries in terms of the ratio of pension fund assets to GDP, which in 2024 amounted to only 0.3 %, compared to 8-12 % in Poland and the Czech Republic and over 40 % in Germany. The developed scenarios of system development indicate the possibility of achieving the level of 2-3 % of GDP in the medium term, which would provide a substantial investment resource for the economy. The scientific novelty of the paper lies in combining a quantitative assessment of the effectiveness of private pension funds with scenario forecasting, which made it possible to determine the critical threshold of their development. The practical significance of the results is revealed in the possibility of using the findings to improve regulatory policy, increase public trust in private pension provision, and expand the use of pension savings as a source of financing for Ukraine’s economic recovery.